2006
DOI: 10.1057/palgrave.mel.9100168
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the Relative Efficiency of Container Terminals of Mercosur using DEA

Abstract: Maritime transport is extremely important for the world economy, and similarly for the Brazilian economy. The objective of this paper is to analyse the relative efficiency of operations in container terminals of Mercosur in the years of 2002, 2003 and 2004, using the data envelopment analysis technique in a model BCC, with five inputs (number of cranes, number of berths, number of employees, terminal area, amount of yard equipment) and two outputs (TEUs handled and average number of containers handled per hour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(34 citation statements)
references
References 26 publications
(27 reference statements)
0
33
0
1
Order By: Relevance
“…Land (size of the terminal area), equipment (facilities, buildings, and cargo lifting equipment), labor (the expenses of employees of the port authorities, stevedores, and other types of labor), and management capability are considered to be significant factors affecting container port productivity [8,35]. According to past studies, container terminal area, the berth length, and the number of equipment such as quayside gantries, yard gantries, and straddle carriers, are usually used as input variables, while container throughput is used as the main output variable [8][9][10][11][36][37][38][39][40][41].…”
Section: Input and Outputmentioning
confidence: 99%
“…Land (size of the terminal area), equipment (facilities, buildings, and cargo lifting equipment), labor (the expenses of employees of the port authorities, stevedores, and other types of labor), and management capability are considered to be significant factors affecting container port productivity [8,35]. According to past studies, container terminal area, the berth length, and the number of equipment such as quayside gantries, yard gantries, and straddle carriers, are usually used as input variables, while container throughput is used as the main output variable [8][9][10][11][36][37][38][39][40][41].…”
Section: Input and Outputmentioning
confidence: 99%
“…Numerous studies have discussed the success of the port reforms in the region (Hoffmann, 2001;Kent and Hochstein, 1998;Tongzon and Heng, 2005;Estache et al, 2002;. Efficiency gains from port reform in the Latin American Caribbean port system have been widely studied (Morales et al, 2013, Estache, et al, 2004Barros, et al, 2012;Rios and Maçada, 2006;Wilmsmeier et al, 2006). While these studies identify advances and improvements in port efficiency through private sector involvement, results in the global literature on the relationship between port efficiency and private sector involvement vary and are sometimes even contradictory as recently discussed by Gong et al (2012) and Bichou (2013).…”
Section: Port Devolution and Productivitymentioning
confidence: 99%
“…The study concluded that most efficient ports are those which are smaller size and managed under a more centralized regime. Rios and Macada [10] analysed the relative efficiency of container terminals of Mercosur using Data Envelopment Analysis. This study found that 60% of the terminals were efficient in the 3-year period.…”
Section: Literature Reviewmentioning
confidence: 99%